Local potential downstreaming and pokdarwis institutional strengthening: Towards a sustainable halal tourism destination - Susanti, Dwi; Muliawanti, Lintang; Pambuko, Zulfikar Bagus; Annisa, Nenden Nur; Praditya, Miftakhul Wahyu Ragil; Luhtitisari, Aurelia Rahma Niken; Nafisah, Najmah; Yunita, Arum (Community Empowerment, 2025)
Sumberarum Village in Magelang Regency possesses significant tourism potential through the hot springs, yet the development of flagship products and institutional capacity remains underdeveloped. This community service program aims to empower local MSMEs and strengthen the Tourism Awareness Group (Pokdarwis) to support the halal tourism village ecosystem. Utilizing the Participatory Rural Appraisal (PRA) method, the program engaged 20 participants from the Village-Owned Enterprise (BUMDes) and Pokdarwis through food processing training, Cost of Goods Sold (COGS) calculation, and tourism management strengthening. Evaluation results indicated a significant increase in participants' knowledge (from 48% to 69%). Based on hedonic tests, the papaya jelly product achieved the highest preference rate (87%). Furthermore, the initiative successfully established the Pokdarwis organizational structure and enhanced the financial literacy of MSME actors. The synergy between local commodity-based product innovation and institutional strengthening proved effective in accelerating community economic independence within the tourism village area.